The creation, diffusion, and reception of Italian art in the early modern Iberian world
1 online resource
Keywords: "This edited volume addresses the circulation of works of art, images, and ideas between the Iberian and Italian world, and the subsequent responses this motion generated. Amongst the themes discussed are the concept of centre and periphery, replicas and alterations, how items and ideas were reinterpreted. The processes of appropriation and transformation create an artistic geography of identities in which originality can be studied through the processes of assimilation of images shared between Europe, Asia and America. Chapters challenge the negative conceptualization of "copying" arguing that the "copy" is not simply a derivation, but a new creation that is shaped by the interests and preferences of the receiver. Similarly, contributors argue for a more nuanced concept of what exactly an artistic centre is. The book will be of interest to scholars working in art history, Renaissance studies, and Iberian studies"--